2017
DOI: 10.1371/journal.pone.0170041
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Camouflaged Earthworm Hemoglobin

Abstract: Nearly 21 million components of blood and whole blood and transfused annually in the United States, while on average only 13.6 million units of blood are donated. As the demand for Red Blood Cells (RBCs) continues to increase due to the aging population, this deficit will be more significant. Despite decades of research to develop hemoglobin (Hb) based oxygen (O2) carriers (HBOCs) as RBC substitutes, there are no products approved for clinical use. Lumbricus terrestris erythrocruorin (LtEc) is the large acellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…All of these properties suggest that gLtEc may be an attractive blood substitute for deployment in battlefield scenarios. Lastly, it is also worth mentioning that a PEGylated LtEc developed by Roche et al has a dramatically increased circulation half‐life (66.8 ± 1.8 h) compared to native LtEc (18 ± 0.8 h) . Taken together, both LtEc derivatives demonstrate that LtEc can be synthetically modified to make it an even more attractive blood substitute.…”
Section: Resultsmentioning
confidence: 99%
“…All of these properties suggest that gLtEc may be an attractive blood substitute for deployment in battlefield scenarios. Lastly, it is also worth mentioning that a PEGylated LtEc developed by Roche et al has a dramatically increased circulation half‐life (66.8 ± 1.8 h) compared to native LtEc (18 ± 0.8 h) . Taken together, both LtEc derivatives demonstrate that LtEc can be synthetically modified to make it an even more attractive blood substitute.…”
Section: Resultsmentioning
confidence: 99%
“…Still, physiological in vivo "proof of concept" was missing. In the context of AOC development, normovolemic hemodilution of the rat is a well-established model to test functionality of a novel AOC [16][17][18][19] . Consequently, we used the model of massive hemodilution in the rat to determine the physiological functionality of our capsules.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we used a rat model of massive hemodilution, where we exchanged about 95% of the blood volume with either capsules in a plasma-like solution (treatment) or the plasma-like solution without capsules (control) and posthumously surveyed hypoxia sensitive organs such as the small intestine and kidney. In the context of AOC development, normovolemic hemodilution of the rat is a well-established model to test their functionality [16][17][18][19] . Our study is aimed at serving as a "proof of concept" that capsules are a life-saving erythrocyte substitute, thereby avoiding the onset of tissue hypoxia even at critically low hematocrit.…”
mentioning
confidence: 99%
“…Preclinical studies in mice, rats, and hamsters have already shown that both LtEc and AmEc effectively deliver O 2 in vivo without the significant increase in mean arterial pressure observed with some other HBOCs . The circulation half‐life of both LtEc and AmEc are limited to 12 hours, but PEGylation of LtEc has been shown to increase its half‐life up to 70 hours . Transfusions of LtEc and AmEc also do not elicit any changes in animal behavior or health for several months after the initial injection .…”
Section: Discussionmentioning
confidence: 99%